Combining scanning tunneling microscope (STM) imaging and local manipulation to probe the high dose oxidation structure of the Si(111)-7×7 surface - Richard Cobley (Nano Research, 2020)
Understanding the atomistic formation of oxide layers on semiconductors is important for thin film fabrication, scaling down conventional devices and for the integration of emerging research materials. Here, the initial oxidation of Si(111) is studied using the scanning tunneling microscope. Prior to the complete saturation of the silicon surface with oxygen, we are able to probe the atomic nature of the oxide layer formation. We establish the threshold for local manipulation of inserted oxygen sites to be +3.8 V. Only by combining imaging with local atomic manipulation are we able to determine whether inserted oxygen exists beneath surface-bonded oxygen sites and differentiate between sites that have one and more than one oxygen atom inserted beneath the surface. Prior to the creation of the thin oxide film we observe a flip in the manipulation rates of inserted oxygen sites consistent with more oxygen inserting beneath the silicon surface.